THE MOUNT MARAPI ERUPTION DISASTER EVACUATION PATH MODEL USING A LOCAL WISDOM APPROACH - Purwaningsih, Endah; Liusti, Siti Ainim; Purnamasari, Eva; Ramadhan, Risky; Nasution, Aulia Fajrin Ramadhani (GEOMATE Journal, 2024)
This research focuses on the slopes of an active volcano, seeing its importance in studying disaster mitigation, especially evacuation routes, to minimize fatality during a volcanic eruption. Determining evacuation routes using local wisdom is used as a guide for communities around the mountain slopes to safeguard themselves in the event of a mountain eruption. This research aims to model an eruption disaster evaluation pathway using a local wisdom approach. This research employs a mixed-method approach, combining quantitative and qualitative methods to process and analyze relevant variables. The ultimate output is a map illustrating volcanic disaster evacuation routes. For vulnerability analysis related to volcanic disasters, this research uses quantitative methods with the Maximum Entropy algorithm. The research identifies slope as the environmental variable with the highest gain when used in isolation, suggesting its significant informational value. The modeling used was in the 12th iteration of 25 model test replications, with AUC training data reaching a value of 0.877 and AUC test data of 0.932, indicating highly effective modeling results. In addition, the local wisdom from the community plays a crucial role in recognizing impending eruption signs, with an emphasis on observing natural symptoms in the surrounding environment. The people of Nagari Batu Palano do not have specific social traditions related to volcanic eruptions. Instead, their primary response involves surrendering to God and seeking a safe place if an eruption occurs. In relation to saltwater pools, there is a need for further studies to establish the reliability of the information produced.